Wnt5a promotes hippocampal postsynaptic development and GluN2B-induced expression via the eIF2α HRI kinase - Ramos-Fernandez, Eva; Arrazola, Macarena S.; Oliva, Carolina A.; Arredondo, Sebastian B.; Varela-Nallar, Lorena; Inestrosa, Nibaldo C. (My University, 2021)
Wnt signaling plays a key role in neurodevelopment and neuronal maturation. Specifically, Wnt5a stimulates postsynaptic assemblies, increases glutamatergic neurotransmission and, through calcium signaling, generates nitric oxide (NO). Trying to unveil the molecular pathway triggering these postsynaptic effects, we found that Wnt5a treatment induces a time-dependent increases in the length of the postsynaptic density (PSD), elicits novel synaptic contacts and facilitates F-actin flow both in in vitro and ex vivo models. These effects were partially abolished by the inhibition of the Heme-regulated eukaryotic initiation factor 2 alpha (HRI) kinase, a kinase which phosphorylates the initiation translational factor eIF2 alpha. When phosphorylated, eIF2 alpha normally avoids the translation of proteins not needed during stress conditions, in order to avoid unnecessary energetic expenses. However, phosphorylated eIF2 alpha promotes the translation of some proteins with more than one open reading frame in its 5 ' untranslated region. One of these proteins targeted by Wnt-HRI-eIF2 alpha mediated translation is the GluN2B subunit of the NMDA receptor. The identified increase in GluN2B expression correlated with increased NMDA receptor function. Considering that NMDA receptors are crucial for excitatory synaptic transmission, the molecular pathway described here contributes to the understanding of the fast and plastic translational mechanisms activated during learning and memory processes.
Keywords: Postsynaptic density